Will global imbalances decrease or even increase? - Jens Boysen-Hogrefe; Klaus-Jürgen Gern; Nils Jannsen (The crisis and beyond, 2009)
Assessing the quantitative impact of the fiscal packages which have been adopted in the current financial crisis is extremely difficult. The studies which are presented in this paper show wide differences, both for short-term and for medium-term multipliers. Moreover, multipliers which are derived from past experience may not apply in the current financial crisis. There are three main reasons: the zero-bound for monetary policy which played almost no role in the past has become binding in many countries; the standard procedure of calculating multipliers on the assumption of being in an initial equilibrium position is hardly appropriate in the current deep recession; and the standard procedure of linearizing models is questionable as currently there is a substantial deviation from the equilibrium.
Keywords: 330; Finanzmarktkrise; Wirtschaftskrise; Leistungsbilanz; Zahlungsbilanzungleichgewicht; Welt